STRATEGI PEMBERDAYAAN MASYARAKAT MELALUI KELOMPOK USAHA BUDIDAYA LEBAH MADU DALAM MENINGKATKAN KEMANDIRIAN EKONOMI KELUARGA DESA SANGKANMANIK - Siti Puji Paujiah; Sudadio; Sholih (Politeknik Negeri Sriwijaya, 2023)
One of the efforts to become an economically independent community is through community empowerment by utilizing natural resources, namely honey bee cultivation in Sangkanmanik Village, Cimarga District, Lebak Regency. This study aims to describe: 1) community empowerment strategies 2) community empowerment results 3) supporting and inhibiting factors of community empowerment. In this study the method used is descriptive method and qualitative approach, data obtained from observations, interviews and documentation. The data sources in this study consisted of six people, namely one chief executive and group leader and five members of the honey bee cultivation business group. Based on the results of the study it was found that 1) The community empowerment strategy carried out by the head of the honey bee cultivation business group was (1) facilitating venture capital, (2) community awareness, (3) providing knowledge (4) providing motivation (5) group management. 2) The results of community empowerment through the honey bee cultivation business group are increasing family economic resources so that economic and social needs are met, although not yet optimal. 3) Supporting factors in the implementation of community empowerment are human resources, strong motivation and government policies. The obstacles to empowering the community in the honey bee cultivation business are weak assistance, delays in science and technology, and the attitudes of people who are still traditional.